Opportunistic and non-opportunistic intestinal parasites in HIV/ AIDS patients in relation to their clinical and epidemiological status in a specialized medical service in Goiás, Brazil - Barcelos, Natane Barbosa; Silva, Lorena de Freitas e; Dias, Regyane Ferreira Guimarães; Menezes Filho, Hélio Ranes de; Rodrigues, Rosângela Maria (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Patients infected with the Human Immunodeficiency Virus (HIV) often have opportunistic infections, among which strongyloidiasis and coccidiosis are the most common parasitic infections that aggravate their health status. This study examined the prevalence of intestinal parasites, particularly of Strongyloides stercoralis and intestinal coccidia in patients with the Human Immunodeficiency Virus (HIV)/ Acquired Immunodeficiency Syndrome (AIDS) who were treated at the Specialized Assistance Service (SAE) of Jataí, State of Goiás, Brazil, and analyzed its correlation with clinical, laboratory, and socio-epidemiological parameters. A total of 270 stool samples were analyzed by the Lutz technique, Rugai’s method, Agar Plate Culture, Ritchie’s method and specific staining, Ziehl-Neelsen modified technique, Kinyoun’s method and the rapid safranin method. The prevalence of intestinal parasites was 28.88% including 3.8% of S. stercoralis, Cryptosporidium sp. and Cystoisospora belli. There was a significant positive correlation between intestinal parasites and the clinical status and the use of antiretroviral therapy (ART), smoking, CD4+ lymphocyte counts and sexual orientation. In conclusion, the widespread use of antiretroviral therapy and health assistance contributed to the low prevalence of S. stercoralis and coccidiosis in patients with HIV/ AIDS who were followed up at the SAE.